Mercury (II) adsorption process from an aqueous solution through activated carbon blended with fresh pistachio green shell powder - Reza Davarnejad; Saeedeh Afshar; Masoud Pirhadi; Matineh Mirhosseini (Scientific Reports)
Abstract In this research, fresh pistachio green shell as an agricultural waste was blended with activated carbon to study the adsorption process of mercury (II) from several aqueous solutions with various concentrations. Central Composite Design under Response Surface Methodology was statistically used to consider the independent variables involving pH, contact time, fresh pistachio green shell powder dosage, initial concentration of mercury (II) and activated carbon dosage effects on the mercury (II) removal. pH of 6.13, initial mercury (II) concentration of 36.68 g/l, fresh pistachio shell powder dosage of 9.21 g/l, activated carbon dosage of 7.25 g/l as an optimal operating conditions for 99.25% of mercury (II) removal was experimentally found. The adsorption kinetic models such as the pseudo-first order, pseudo-second order, Elovich, and intraparticle diffusion were examined. The pseudo-second-order model (with R2 ≈ 1) could properly investigate the adsorption process kinetics. The adsorption isothermal behavior was considered using the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherm models. Langmuir isotherm model showed the best results demonstrating the blended adsorbent homogeneous surface. The activation energy for the adsorption process was obtained at 2.158 kJ/mol. Several morphological tests (such as SEM, XRD, FTIR and EDX) were done to investigate the porosity and surface area of adsorbent although interaction of surface functional groups and synergistic effects can also be considered by these tests. The fresh pistachio green shell powder blended with activated carbon could physically adsorb (physisorption process) mercury (II) from an aqueous wastewater.